Sodium Transition Metal Polyanions
By adopting sodium transition metal multivariate anions with a specific crystal structure as the positive electrode active material and preparing it by hydrothermal treatment, the problem of low discharge capacity of existing sodium iron phosphate is solved, and the performance of efficient sodium secondary battery is achieved.
Patent Information
- Application Number
- JP2021033292
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-04
- Filing Date
- 2021-03-03
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-03-03
AI Technical Summary
The existing sodium-ferrous phosphate (NaFePO) is a sodium secondary battery with positive electrode active material, and the discharge capacity is only about 60 mAh/g, and the performance is not ideal.
The sodium transition metal polyanion (Na3M3(PO4)4) with a specific crystal structure and coordination composition is used as the positive electrode active material, and the crystal structure and crystal diameter are prepared by hydrothermal treatment to control the crystal structure and crystal diameter to improve the insertion and detachment efficiency of sodium.
The discharge capacity of sodium secondary batteries is significantly improved, achieving or exceeding the performance of traditional sodium secondary batteries, and showing high charge and discharge characteristics in non-aqueous and water-based batteries.
Smart Images

Figure 0007669722000001 
Figure 0007669722000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to novel sodium transition metal polyanions and methods for their preparation. [Background technology]
[0002] Sodium secondary batteries do not use lithium, a rare metal, and are therefore attracting attention as post-lithium secondary batteries. As a positive electrode active material for sodium secondary batteries, sodium transition metal-containing materials containing a counter anion such as a transition metal oxide, polyanion, or fluoride and sodium are being considered. Among sodium transition metal-containing materials, sodium-containing transition metal polyanions are expected to exhibit high charge / discharge capacity.
[0003] For example, it has been reported that sodium iron phosphate (NaFePO4), a sodium-containing transition metal phosphate compound having an olivine structure, undergoes a reversible insertion / extraction reaction of Na cations (for example, Patent Document 1). However, the discharge capacity obtained remains low at about 60 mAh / g. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2009-206085 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present disclosure is to provide at least one of a novel sodium transition metal polyanion, a positive electrode active material and a sodium secondary battery containing the same, and methods for producing these. [Means for solving the problem]
[0006] In the present disclosure, the present inventors have discovered a novel sodium transition metal polyanion, which can be used as a positive electrode active material for sodium secondary batteries, and further discovered that a sodium secondary battery using the sodium transition metal polyanion as a positive electrode material exhibits a higher discharge capacity than conventional sodium secondary batteries.
[0007] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A powder X-ray diffraction pattern represented by the general formula Na3M3(PO4)4 (wherein M is one or more selected from the group consisting of Fe, Mn, Ni, and Co), a monoclinic crystal structure, and lattice constants, each of which is: a is 19.45 Å or more and 19.75 Å or less, b is 6.30 Å or more and 6.45 Å or less, and c is 10.45 Å or more and 10.75 Å or less, A sodium transition metal polyanion, characterized in that β is 90.1° or more and 93.3° or less. [2] The sodium transition metal polyanion according to the above [1], wherein the lattice constants are a: 19.63 Å or less, b: 6.38 Å or less, or β: 91.5° or less. [3] The sodium transition metal polyanion according to the above [1] or [2], wherein the monoclinic crystal is a monoclinic crystal belonging to the space group C2 / c. [4] The sodium transition metal polyanion according to any one of the above [1] to [3], which contains at least one selected from the group consisting of manganese, nickel and cobalt, and iron. [5] The sodium transition metal polyanion according to at least any one of the above [1] to [4], wherein the proportion of a powder X-ray diffraction pattern represented by the general formula Na3M3(PO4)4 (wherein M is one or more selected from the group consisting of Fe, Mn, Ni, and Co) in the powder X-ray diffraction pattern of the sodium transition metal polyanion is 80% or more. [6] The sodium transition metal polyanion according to any one of [1] to [5] above, which comprises a coating layer. [7] A method for producing a sodium transition metal polyanion according to any one of [1] to [6] above, comprising a step of subjecting a composition containing a sodium source, a transition metal source, a phosphate source and water and having a pH of 4.0 or more and 11.0 or less to hydrothermal treatment at 140°C or more and 250°C or less. [8] The method for producing the present invention described in [7] above, wherein the pH is 6.0 or higher and 9.0 or lower. [9] The method according to [7] or [8] above, wherein the transition metal source is one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, phosphates, sulfites, sulfates, nitrates, chlorides, acetates, bromides and fluorides containing one or more elements selected from the group consisting of Fe, Mn, Ni and Co.
[10] A positive electrode active material comprising the sodium transition metal polyanion according to any one of [1] to [6] above.
[11] A sodium secondary battery comprising a positive electrode containing the sodium transition metal polyanion according to any one of [1] to [6] above, a negative electrode, and an electrolyte.
[12] The sodium secondary battery according to the above
[11] , wherein the negative electrode contains at least NaTi2(PO4)3.
[13] The sodium secondary battery according to the above
[11] or
[12] , wherein the electrolyte contains at least NaClO4.
[14] The sodium secondary battery according to any one of the above
[11] to
[13] , wherein the electrolytic solution is an aqueous electrolytic solution.
[15] The sodium secondary battery according to any one of the above
[11] to
[13] , wherein the electrolytic solution is a non-aqueous electrolytic solution. Effect of the Invention
[0008] The present disclosure makes it possible to provide at least one of a novel sodium transition metal polyanion, a positive electrode active material containing the same, a sodium secondary battery, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1]Powder X-ray diffraction pattern of the sodium iron polyanion of Example 1. [Diagram 2] Powder X-ray diffraction pattern of the sodium iron polyanion of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Sodium transition metal polyanion> The sodium transition metal polyanion of the present disclosure will be described below with reference to an example of an embodiment.
[0011] The sodium transition metal polyanion of this embodiment is a sodium transition metal polyanion having a powder X-ray diffraction pattern represented by the general formula Na3M3(PO4)4 (M is one or more selected from the group consisting of Fe, Mn, Ni, and Co), a monoclinic crystal structure, and lattice constants a of 19.45 Å to 19.75 Å, b of 6.30 Å to 6.45 Å, c of 10.45 Å to 10.75 Å, and β of 90.1° to 93.3°, respectively.
[0012] In this embodiment, the "sodium transition metal polyanion (hereinafter also referred to as "NaTP", and when the transition metal is iron, also referred to as "sodium iron polyanion" or "NaFeP", etc.)" is a compound consisting of sodium (Na), a transition metal, and two or more anions, and is preferably an artificially synthesized compound, i.e., a synthetic sodium transition metal polyanion.
[0013] The transition metal contained in NaTP of this embodiment is one or more selected from the group consisting of iron (Fe), manganese (Mn), nickel (Ni) and cobalt (Co), one or more selected from the group consisting of iron, manganese and nickel, at least one of iron and manganese, or even iron. NaTP of this embodiment preferably contains iron, and may contain one or more selected from the group consisting of manganese, nickel and cobalt and iron, or may contain at least one of manganese and cobalt and iron. Furthermore, NaTP of this embodiment may contain at least one or more selected from the group consisting of manganese, nickel and cobalt.
[0014] The anion is the phosphate ion (PO4 3- ) is preferred.
[0015] In this embodiment, NaTP is a hydrogen phosphate ion (HPO4 2- ) hydroxide ion (OH - ), chloride ion (Cl - ), bromide ion (Br - ), sulfate ion (SO4 2- ) and nitrate ion (NO3 - ) and more preferably does not contain chloride ions.
[0016] The NaTP of this embodiment has a powder X-ray diffraction pattern (hereinafter also referred to as "XRD pattern") represented by the general formula Na3M3(PO4)4 (M is one or more selected from the group consisting of Fe, Mn, Ni, and Co). The XRD pattern may be measured using a general powder X-ray diffractometer. The following conditions can be exemplified as preferred measurement conditions for the XRD pattern. Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Step scan Scan condition: 20° / min Measurement time: 3 seconds 2θ: 5° to 90°
[0017] The presence and the proportion of the XRD pattern (hereinafter also referred to as the "main XRD pattern") represented by the general formula Na3M3(PO4)4 (M is one or more selected from the group consisting of Fe, Mn, Ni, and Co) can be confirmed by comparing (fitting) the main XRD pattern (hereinafter also referred to as the "simulation pattern") obtained by simulation with the measured XRD pattern of NaTP of this embodiment by Rietveld analysis. The simulation pattern may be an XRD pattern obtained by calculation of Na3Fe3(PO4)4 or a compound in which Fe in Na3Fe3(PO4)4 is replaced with any transition metal (M, i.e., one or more selected from the group consisting of Fe, Mn, Ni, and Co). A preferred simulation pattern used in fitting NaTP of this embodiment is the XRD pattern of Na3Fe3(PO4)4 described in Materials Research Bulletin 37 (2002) 2407-2416 (hereinafter also referred to as the "reference literature"). In this embodiment, the XRD pattern can be used as a simulation pattern in fitting NaTP containing at least Fe.
[0018] With respect to NaTP of this embodiment, "having a main XRD pattern" means that the main XRD pattern can be confirmed in the XRD pattern obtained by XRD measurement of NaTP of this embodiment, i.e., the main XRD pattern is included.
[0019] In the present embodiment, the proportion of the main XRD pattern in the XRD pattern of NaTP (hereinafter, also referred to as "purity") is 80% or more, preferably 90% or more, and more preferably 99% or more. When the XRD pattern of NaTP of the present embodiment is only the main XRD pattern, the purity is 100%. It is permissible for NaTP of the present embodiment to contain a small amount of by-product phase, that is, a by-product phase to an extent that does not inhibit desorption and insertion of sodium. Therefore, the purity may be 100% or less, or even less than 100%. The purity in the present embodiment can be determined by the reference intensity ratio (hereinafter, also referred to as "RIR") method. Specifically, the purity can be determined by the ratio of area intensities in the comparison between the XRD pattern and the above-mentioned simulation pattern by Rietveld analysis.
[0020] The NaTP of the present embodiment has a monoclinic crystal structure, preferably belonging to the space group C2 / c. A monoclinic crystal structure has different lattice constants a, b, and c, and also has α and γ both at 90° and β at different values (i.e., other than 90°).
[0021] The lattice constants of NaTP of this embodiment are a 19.45 Å to 19.75 Å, preferably 19.55 Å to 19.65 Å, b 6.30 Å to 6.45 Å, preferably 6.35 Å to 6.40 Å, and c 10.45 Å to 10.75 Å, preferably 10.55 Å to 10.65 Å, and β 90.1° to 93.3°, preferably 90.3° to 93.3°, more preferably 91.3° to 92.3°. For example, the lattice constants of NaTP of this embodiment, and further the NaTP containing Fe of this embodiment, are a 19.63 Å or less, b 6.38 Å or less, or β 91.5° or less.
[0022] For example, the lattice constant of NaFeP (sodium iron polyanion) of this embodiment is a is 19.50 Å or more, 19.60 Å or more, or 19.61 Å or more, and 19.75 Å or less, or 19.63 Å or less; b is 6.30 Å or more or 6.31 Å or more and 6.40 Å or less or 6.38 Å or less; c is 10.50 Å or more, or 10.52 Å or more, and 10.70 Å or less, 10.60 Å or less, or 10.57 Å or less, and β is 90.1° or more, 90.2° or more, or 90.3° or more, and 92.0° or less, 91.5° or less, or 91.0° or less. The lattice constant of NaFeP (sodium iron polyanion) of this embodiment is a is 19.63 Å or less, b is 6.38 Å or less, or β is 91.5° or less.
[0023] The lattice constants of NaFeMnP (sodium iron manganese polyanion) of this embodiment can be, for example, a of 19.65 Å or more and 19.75 Å or less, b of 6.35 Å or more and 6.45 Å or less, c of 10.63 Å or more and 10.73 Å or less, and β of 90.3° or more and 91.0° or less.
[0024] The lattice constants of NaFeCoP (sodium iron cobalt polyanion) of this embodiment can be exemplified as follows: a is 19.65 Å or more and 19.75 Å or less, b is 6.40 Å or more and 6.45 Å or less, c is 10.60 Å or more and 10.80 Å or less, and β is 90.3° or more and 90.6° or less.
[0025] The lattice constant can be determined by comparing (fitting) the XRD pattern of NaTP of this embodiment with a simulation pattern by Rietveld analysis.
[0026] The NaTP of the present embodiment has both such purity and crystal structure, and is therefore expected to facilitate the insertion and desorption of sodium ions compared to conventional NaTP, thereby resulting in the development of high charge / discharge characteristics.
[0027] The crystallite diameter of the NaTP of this embodiment is preferably 20 Å or more and 1500 Å or less, and for example, the crystallite diameter of NaTP containing Fe is 20 Å or more or 40 Å or more and 200 Å or less or 150 Å or less. With a purity of 80% or more and a crystallite diameter within this range, the NaTP of this embodiment is more likely to efficiently intercalate and deintercalate sodium, and is expected to exhibit high charge / discharge capacity as a positive electrode active material for a sodium secondary battery.
[0028] In this embodiment, the "crystallite size" is a size (hereinafter also referred to as "WH size") obtained by the Williamson-Hall method from two or more XRD peaks belonging to the XRD pattern of the general formula Na3M3(PO4)4 (M is one or more selected from the group of Fe, Mn, Ni, and Co). Specifically, the following plots are made for two or more XRD peaks that can be assigned to the general formula Na3M3(PO4)4 (M is one or more selected from the group of Fe, Mn, Ni, and Co), and further for all XRD peaks that can be assigned to the general formula Na3M3(PO4)4 (M is one or more selected from the group of Fe, Mn, Ni, and Co). The following linear approximation formula is obtained by the least squares method of the obtained plots of multiple points, and the reciprocal of the y-intercept of the linear approximation formula is the crystallite size.
[0029] <Plot> Y=(β sinθ) / λ X=sinθ / λ <First-order approximation formula> Y = 2η·X + (1 / ε) (1 equation) In these formulas, β is the half-width (°), θ is the diffraction angle (°), λ is the wavelength of the radiation source (nm), η is the non-uniform distortion, and ε is the crystallite diameter (Å), and 1 / ε in the linear approximation formula is the y-intercept. In addition, in the calculation of the WH diameter in this embodiment, there is no particular limitation on the XRD peak to be used, and for example, all XRD peaks that belong to NaTP may be used.
[0030] The NaTP of this embodiment may have one or more layers (hereinafter also referred to as "coating layers") selected from the group consisting of metals, fluorine, fluoride, phosphorus, phosphorus compounds, metal oxides, carbon, compounds containing carbon, and conductive polymers on a part or all of the surface. The coating layer tends to increase the conductivity of NaTP. The coating layer is preferably one or more layers selected from the group consisting of compounds containing carbon, carbon, and conductive polymers, and is more preferably a carbon layer. The coating layer does not have to cover the entire surface of NaTP.
[0031] The form of the NaTP of this embodiment may be any form, and examples thereof include one or more forms selected from the group consisting of powder, granules, and molded bodies, with powder being preferred.
[0032] The NaTP of the present embodiment is a sodium ion (Na + Since the insertion and desorption of ions into and from the cations of the compound easily proceeds, the compound can be used as an adsorbent, an ion exchanger, a hydrogen ion conductor, a solid electrolyte, a battery material, and the like, and further can be used as an active material for electrochemical devices, in particular as a positive electrode active material for sodium secondary batteries, and further as a positive electrode active material for aqueous sodium secondary batteries. <Method of producing sodium transition metal polyanion> The method for producing the sodium transition metal polyanion of this embodiment will be described below.
[0033] The NaTP of the present embodiment can be obtained by a production method comprising the step of subjecting a composition containing a sodium source, a transition metal source, a phosphate source, and water and having a pH of 4.0 or more and 11.0 or less to hydrothermal treatment at 140° C. or more and 250° C. or less.
[0034] By subjecting a composition (hereinafter also referred to as the "raw material composition") containing a sodium source, a transition metal source, a phosphate source, and water and having a pH of 4.0 or more and 11.0 or less to a hydrothermal treatment process (hereinafter also referred to as the "hydrothermal treatment process"), the production of by-product phases can be significantly suppressed, and NaTP of the present embodiment can be obtained.
[0035] The sodium source is at least one of a compound containing sodium (Na) and sodium, and is preferably a water-soluble sodium salt. Preferred examples of the sodium source include one or more selected from the group consisting of sodium fluoride, sodium chloride, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium sulfite, sodium sulfate, sodium hydrogen carbonate, and sodium carbonate, or one or more selected from the group consisting of sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, sodium sulfite, sodium sulfate, sodium hydrogen carbonate, and sodium phosphate, and one or more selected from the group consisting of sodium phosphate, sodium hydrogen phosphate, and disodium hydrogen phosphate.
[0036] The phosphate source is a compound containing phosphate ions, and is preferably at least one of water-soluble phosphoric acid and phosphate salts. Preferred phosphate sources include one or more selected from the group consisting of orthophosphoric acid, sodium phosphate, disodium hydrogen phosphate, ammonium phosphate, lithium phosphate, and potassium phosphate, and further one or more selected from the group consisting of orthophosphoric acid, sodium phosphate, sodium hydrogen phosphate, and disodium hydrogen phosphate.
[0037] The raw material composition preferably contains sodium phosphate as a source of phosphoric acid and sodium.
[0038] The transition metal source is a compound containing one or more selected from the group consisting of iron (Fe), manganese (Mn), nickel (Ni) or cobalt (Co), a compound containing at least one of iron, manganese and nickel, a compound containing at least one of iron or manganese, or a compound containing iron. The transition metal source is preferably one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, sulfites, sulfates, phosphates, carbonates, nitrates, chlorides and acetates containing one or more selected from the group consisting of iron, manganese, nickel and cobalt, more preferably at least one of sulfates, phosphates or carbonates, and more preferably phosphates. Examples of preferred transition metal sources include one or more selected from the group consisting of sulfates, phosphates and carbonates containing at least iron, and further phosphates containing at least iron. The transition metal source may also contain at least one selected from the group consisting of manganese, nickel and cobalt.
[0039] The transition metal contained in the transition metal source is one or more selected from the group consisting of iron, manganese, nickel and cobalt, preferably one or more selected from the group consisting of iron, manganese and nickel, more preferably at least one of iron or manganese, and more preferably iron.
[0040] The iron-containing raw material composition preferably contains at least iron phosphate as a phosphate source and a transition metal source.
[0041] Examples of water include pure water, ion-exchanged water, and water derived from other raw materials (for example, hydrates, structured water, aqueous solutions, etc.).
[0042] The raw material composition may contain additives in addition to the sodium source, transition metal source, and phosphate source, and water. The additives may be, for example, one or more selected from the group consisting of oxalic acid, ascorbic acid, sulfurous acid, sodium sulfite, thiosulfate, sodium thiosulfate, sodium hydrogen monosulfide, hydrazine, and sodium hypochlorite, or one or more selected from the group consisting of ascorbic acid, sulfurous acid, sodium sulfite, thiosulfate, sodium thiosulfate, sodium hydrogen monosulfide, and sodium hypochlorite.
[0043] The pH of the raw material composition is from 4.0 to 11.0, preferably from 5.0 to 10, and more preferably from 6.0 to 9.0. The pH of the raw material composition containing iron is, for example, from 6.0 to 6.1, and from 8.0 to 7.5, or from 7.0 to 7.0.
[0044] The raw material composition can be obtained by mixing the raw materials, water, and, if necessary, additives so as to have a uniform composition, by any method.
[0045] The hydrothermal treatment is preferably carried out by filling the raw material composition into a reaction vessel. The reaction vessel is not particularly limited as long as it can be used in the raw material composition and the hydrothermal treatment step used in this embodiment, and examples of the reaction vessel include a sealed pressure-resistant vessel whose inner surface is coated with Teflon (registered trademark) resin or fluororesin.
[0046] The hydrothermal treatment temperature is 140° C. or more and 250° C. or less, further 150° C. or more and 250° C. or less, further 170° C. or more and 250° C. or less, and further more more than 180° C. and 250° C. or less, and preferably 190° C. or more and 230° C. or less. In addition, the hydrothermal treatment temperature of the iron-containing raw material composition can be, for example, 150° C. or more or 170° C. or more and 200° C. or less or 180° C. or less.
[0047] Preferred hydrothermal treatment conditions, particularly for a raw material composition containing iron, include a hydrothermal treatment temperature of 140° C. or higher and 230° C. or lower, and a pH of 5.5 or higher and 7.5 or lower. The time for the hydrothermal treatment depends on the hydrothermal treatment temperature. For example, when the hydrothermal treatment temperature is 100° C. or less, the time is 10 hours or more and 200 hours or less, and when the hydrothermal treatment temperature exceeds 100° C., the time is 3 hours or more and 5 hours or more, and 50 hours or less, 20 hours or less, or 10 hours or less, can be exemplified.
[0048] The manufacturing method of this embodiment may include at least one step selected from the group consisting of a washing step, a separation step, and a drying step.
[0049] The washing step is a step of removing impurities from NaTP. Any washing method can be used, but an example of the washing method is a treatment in which NaTP is dispersed in a sufficient amount of pure water. This treatment may be carried out multiple times.
[0050] The separation step is a step of separating NaTP from the solvent by any method, and may be, for example, one or more methods selected from the group consisting of centrifugal sedimentation, filtration, and filter press.
[0051] The drying step is a step of removing moisture adsorbed to NaTP. Any drying method may be used, including treatment in air or in vacuum at 80° C. to 120° C. for 1 hour to 24 hours, and preferably treatment in vacuum.
[0052] Furthermore, the manufacturing method of this embodiment may include a coating step of forming a coating layer on NaTP. The method of forming a coating layer on NaTP is not particularly limited, but examples thereof include a method of subjecting a precursor of the coating layer and NaTP to mechanical milling or a method of thermal decomposition. In addition, when a carbon layer is formed on the surface of NaTP as a coating layer, a method of subjecting NaTP and acetylene black to mechanical milling in an inert atmosphere or a method of subjecting NaTP and sucrose (C 12 H 22 O 11 ) are mixed together, and then heat-treated in an inert atmosphere.
[0053] <Cathode active material> Next, a positive electrode active material containing the sodium transition metal polyanion of the present disclosure will be described with reference to an example of an embodiment. In this embodiment, the "positive electrode active material" refers to an electrode active material of an electrode having a higher potential among the electrodes constituting an electrochemical device, and in particular, an electrode active material of a positive electrode of a sodium secondary battery.
[0054] The positive electrode active material of the present embodiment may contain only the NaTP of the present embodiment, or may contain a sodium transition metal compound other than the NaTP of the present embodiment. The mass ratio of NaTP to the mass of the positive electrode active material of the present embodiment is 80 mass% or more and 100 mass% or less, preferably 90 mass% or more and 100 mass% or less, and more preferably 100 mass% (the positive electrode active material is only NaTP). The positive electrode active material of this embodiment may have a coating layer, such as a carbon layer, on a part or the whole of the surface of the positive electrode active material, preferably a coating layer having electrical conductivity.
[0055] <Sodium secondary battery> Next, a sodium secondary battery comprising a positive electrode containing the sodium transition metal polyanion of the present disclosure, a negative electrode, and an electrolyte solution will be described with reference to an example of an embodiment.
[0056] In this embodiment, the term "sodium secondary battery" refers to a battery that uses sodium ions (Na + A sodium secondary battery is an electrochemical device in which charging and discharging occurs through the insertion and removal of ions, and is synonymous with sodium secondary battery, sodium ion secondary battery, sodium ion battery, sodium storage battery, Na secondary battery, Na ion battery, or Na storage battery.
[0057] A "nonaqueous electrolyte" is an electrolyte that contains a nonaqueous solvent as a solvent, and an "aqueous electrolyte" is an electrolyte that contains an aqueous solvent as a solvent.
[0058] A "nonaqueous sodium secondary battery" is a sodium secondary battery that has a nonaqueous electrolyte as the electrolyte, and an "aqueous sodium secondary battery" is a sodium secondary battery that has an aqueous electrolyte as the electrolyte.
[0059] <Positive electrode> The positive electrode may include a positive electrode mixture containing a positive electrode active material including NaTP according to the present disclosure, and a current collector. The positive electrode mixture contains a positive electrode active material, a binder, a conductive material, and, if necessary, an additive. The binder, the conductive material, and the additive may each be a known material.
[0060] The binder may be one or more selected from the group consisting of fluororesin, polyethylene, polypropylene, SBR material, and imide material, and may further be one or more selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and ethylenetetrafluoroethylene (ETFE).
[0061] The conductive material may be one or more selected from the group consisting of carbon materials, conductive fibers such as metal fibers, metal powders such as copper, silver, nickel, and aluminum, and organic conductive materials such as polyphenylene derivatives. Preferred carbon materials include graphite, soft carbon, hard carbon, carbon black, ketjen black, acetylene black, graphite, activated carbon, carbon nanotubes, carbon fibers, and mesoporous carbon.
[0062] The positive electrode mixture may be produced by a known method, and may be produced by mixing a positive electrode active material, a binder, and a conductive material in a desired ratio.
[0063] <Negative electrode> The negative electrode may include a negative electrode mixture containing a negative electrode active material, a current collector, and, if necessary, an additive. The negative electrode mixture contains a negative electrode active material, a binder, a conductive material, and, if necessary, an additive.
[0064] The negative electrode active material may contain a material that does not prevent the insertion and removal of sodium ions from the positive electrode active material, and may be one or more selected from the group consisting of platinum, zinc, carbon materials, materials that form an alloy with sodium, sodium-containing transition metal oxides, and sodium-containing polyanion materials. Preferred negative electrode active materials may be one or more selected from the group consisting of carbon materials, polyimides, transition metal-containing cyano compounds, and transition metal-containing polyanion compounds. The negative electrode active material is preferably one or more selected from the group consisting of activated carbon, Na2Mn[Mn(CN)6], and NaTi2(PO4)3, and more preferably NaTi2(PO4)3.
[0065] The binder and conductive material may be any known material, and are the same as the binder and conductive material that can be used in the positive electrode mixture described above.
[0066] The negative electrode mixture may be produced by a known method, and may be produced by mixing a negative electrode active material, a binder, and a conductive material in a desired ratio.
[0067] <Electrolyte> The electrolyte is either a non-aqueous electrolyte or an aqueous electrolyte, and is preferably an aqueous electrolyte. The electrolyte is a sodium salt, and a soluble sodium salt is preferable. Preferred electrolytes include one or more selected from the group consisting of NaCl, Na2SO4, NaNO3, NaClO4, NaOH, and Na2S. From the viewpoint of ease of handling, the electrolyte is preferably one or more selected from the group consisting of NaCl, Na2SO4, NaNO3, and NaClO4, and preferably contains NaClO4.
[0068] The electrolyte concentration in the electrolytic solution is not particularly limited, but from the viewpoint of increasing the energy density of the sodium secondary battery, it is preferable that the electrolyte concentration (sodium salt concentration) in the electrolytic solution is high, and an example of the sodium salt concentration is a concentration of 1 mol / kg (1 m) or more and equal to or less than the saturated solubility.
[0069] The electrolyte may contain an additive. The additive is not particularly limited, but may be one or more selected from the group consisting of succinic acid, glutamic acid, maleic acid, citraconic acid, gluconic acid, itaconic acid, diglycol, cyclohexanedicarboxylic acid, cyclopentanetetracarboxylic acid, 1,3-propane sultone, 1,4-butane sultone, methyl methanesulfonate, sulfolane, dimethyl sulfone, and N,N-dimethylmethanesulfonamide. The content of the additive may be, for example, 0.01% by mass or more and 10% by mass or less as a mass ratio of the additive to the mass of the electrolyte. <Other configurations> Other components such as the current collectors of the positive and negative electrodes and the separator may be any known components used in sodium secondary batteries or lithium secondary batteries.
[0070] Another embodiment of the sodium secondary battery of the present disclosure is a battery comprising a positive electrode containing a sodium transition metal polyanion represented by the general formula Na3M3(PO4)4 (wherein M is one or more selected from the group consisting of Fe, Mn, Ni, and Co), a negative electrode, and an electrolyte solution, the negative electrode contains at least NaTi2(PO4)3, and a sodium secondary battery in which the electrolyte contains at least NaClO4.
[0071] Another embodiment of the sodium secondary battery of the present disclosure includes a positive electrode containing a sodium transition metal polyanion represented by the general formula Na3M3(PO4)4, a negative electrode, and an electrolyte, wherein the negative electrode contains at least NaTi2(PO4)3, and a sodium secondary battery in which the electrolyte is an aqueous electrolyte containing at least NaClO4.
[0072] A sodium secondary battery having a positive electrode containing NaTP of this embodiment exhibits a higher charge / discharge capacity than conventional sodium secondary batteries, particularly conventional aqueous sodium secondary batteries. EXAMPLES
[0073] The present disclosure will be specifically described below with reference to examples. However, the present disclosure is not limited to these examples. <Crystal phase identification and composition analysis> The crystal phase of NaTP obtained in the examples was measured by powder X-ray diffraction. Powder X-ray diffraction was measured using a general X-ray diffraction device (device name: SmartLab, manufactured by Rigaku Corporation) under the following conditions.
[0074] Radiation source: CuKα radiation (λ=1.5405Å) Measurement mode: Step scan Scan condition: 20° / min Measurement time: 3 seconds Measurement range: 2θ=5° to 90° The composition ratio of transition metals and sodium metal was determined by Rietvelt analysis using data processing software (product name: PDXL-2) attached to the X-ray diffractometer, and the crystal phase of the product was identified. The simulation pattern in the Rietvelt analysis was determined by calculating the XRD pattern of Na3Fe3(PO4)4 or the XRD pattern of Na3Fe3(PO4)4 with Fe substituted with any M, and comparing the simulation pattern with the measured XRD pattern. Note that the simulation pattern in Examples 1 to 6 used the XRD pattern of Na3Fe3(PO4)4 described in the reference literature. The purity of NaTP was determined from the abundance ratio (area intensity ratio) of the main XRD pattern by the RIR method.
[0075] In addition, the WH size was determined using all XRD peaks assigned to NaTP, and was taken as the crystallite size.
[0076] Example 1 Iron phosphate (FePO4·n hydrate, n=7) and sodium phosphate dodecahydrate (Na3PO4·12H2O) were mixed, and then 85% orthophosphoric acid (H3PO4) and pure water (H2O) were added to obtain the composition shown below.
[0077] Iron phosphate: 4.72g Sodium phosphate dodecahydrate: 4.80g 85% orthophosphoric acid: 0.72g Pure water: 15g The pH of the composition was 7.5.
[0078] The composition was filled into a Teflon (registered trademark) resin container with a lid and sealed, which was then placed in a thermostatic chamber and subjected to a hydrothermal treatment under the following conditions.
[0079] Hydrothermal treatment temperature: 200℃ Hydrothermal treatment time: 16 hours Hydrothermal treatment pressure: Autogenous pressure After the hydrothermal treatment, the product was washed with pure water, filtered, dried at 120°C for 4 hours under vacuum, and then pulverized to obtain a powder of sodium iron polyanion.
[0080] The XRD pattern is shown in Figure 1. The obtained sodium iron polyanion had a purity of 100% (i.e., the XRD pattern of the sodium iron polyanion was only the XRD pattern represented by Na3Fe(PO4)4), and the crystal structure was a monoclinic crystal assigned to the space group C2 / c. The lattice constants were a 19.601(0) Å, b 6.387(0) Å, and c 10.575(0) Å, β 91.810(0)°, and the crystallite size was 54 Å.
[0081] Example 2 The sodium iron polyanion of this example was obtained in the same manner as in Example 1, except that the raw material composition was changed to the following composition.
[0082] Iron phosphate: 4.72g Sodium phosphate dodecahydrate: 4.80g 85% orthophosphoric acid: 1.44g Pure water: 15g The pH of the composition was 7.0.
[0083] The XRD pattern is shown in Figure 2. The obtained sodium iron polyanion had a purity of 100% and a monoclinic crystal structure assigned to the space group C2 / c. The lattice constants were a = 19.716(8) Å, b = 6.378(7) Å, and c = 10.666(7) Å, β = 90.297(0)°, and the crystallite size was 135 Å.
[0084] Example 3 Iron phosphate (FePO4·n hydrate, n=7) and a 7% aqueous solution of sodium phosphate (Na3PO4) were mixed, and then 85% orthophosphoric acid (H3PO4) was added to obtain a composition having the following composition.
[0085] Iron phosphate: 3.30g 7% sodium phosphate solution: 40.0g 85% orthophosphoric acid: 2.06g The pH of the composition was 6.0.
[0086] The composition was filled into a Teflon (registered trademark) resin container with a lid and sealed, which was then placed in a thermostatic chamber and subjected to hydrothermal treatment under the following conditions while rotating at a constant speed of 20 rpm.
[0087] Hydrothermal treatment temperature: 175℃ Hydrothermal treatment time: 9 hours Hydrothermal treatment pressure: Autogenous pressure After the hydrothermal treatment, the product was washed with pure water, filtered, dried at 120°C for 4 hours under vacuum, and then pulverized to obtain a powder of sodium iron polyanion.
[0088] The obtained sodium iron polyanion had a purity of 100% (i.e., the only XRD pattern of sodium iron polyanion was that of Na3Fe(PO4)4), and the crystal structure was monoclinic assigned to the space group C2 / c. The lattice constants were a=19.623(4) Å, b=6.392(7) Å, c=10.646(1) Å, β=92.081(3)°, and the crystallite size was 35 Å.
[0089] Example 4 The sodium iron polyanion of this example was obtained in the same manner as in Example 3, except that the raw material composition was as follows and the hydrothermal treatment temperature was 150°C.
[0090] Iron phosphate: 3.39g 7% sodium phosphate solution: 40.0g 85% orthophosphoric acid: 1.98g The pH of the composition was 6.0.
[0091] The obtained sodium iron polyanion had a purity of 100% (i.e., the only XRD pattern of sodium iron polyanion was that of Na3Fe(PO4)4), and the crystal structure was monoclinic assigned to the space group C2 / c. The lattice parameters were a=19.471(8) Å, b=6.313(2) Å, and c=10.543(2) Å, β=90.518(6)°, and the crystallite size was 117 Å.
[0092] Example 5 The sodium iron manganese polyanion of this example, containing iron and manganese in a ratio of Fe:Mn=3:1, was obtained in the same manner as in Example 3, except that iron phosphate (FePO4 n hydrate, n=7), manganese phosphate (MnPO4 n hydrate), and a 7% aqueous solution of sodium phosphate (Na3PO4) were mixed, and then 85% orthophosphoric acid (H3PO4) was added to obtain a composition having the following composition.
[0093] Iron phosphate: 2.48g Manganese phosphate: 1.02g 7% sodium phosphate solution: 40.0g 85% orthophosphoric acid: 1.96g The pH of the composition was 6.3.
[0094] The resulting sodium iron manganese polyanion was 100% pure (i.e., only the XRD pattern was equivalent to that of Na3Fe3(PO4)4), had a monoclinic crystal structure assigned to the space group C2 / c, had lattice parameters a of 19.732(3) Å, b of 6.398(0) Å, and c of 10.684(3) Å, β of 90.395(4)°, and a crystallite size of 37 Å.
[0095] Example 6 The sodium ferromanganese polyanion of this example, containing iron and cobalt in a ratio of Fe:Co=3:1, was obtained in the same manner as in Example 3, except that iron phosphate (FePO4·n-hydrate, n=7), cobalt phosphate (Co3PO4·octahydrate), and a 7% aqueous solution of sodium phosphate (Na3PO4) were mixed, and then 85% orthophosphoric acid (H3PO4) was added to obtain a composition having the following composition.
[0096] Iron phosphate: 2.48g Cobalt phosphate octahydrate: 2.17g 7% sodium phosphate solution: 40.0g 85% orthophosphoric acid: 1.96g The pH of the composition was 6.2.
[0097] The resulting sodium iron cobalt polyanion was 100% pure (i.e., only the XRD pattern was equivalent to that of Na3Fe3(PO4)4), had a monoclinic crystal structure assigned to the space group C2 / c, and had lattice parameters a=19.743(7) Å, b=6.433(1) Å, and c=10.743(6) Å, β=90.415(8)°, and a crystallite size of 189 Å.
[0098] Measurement example 1 (evaluation of non-aqueous sodium secondary batteries) (Formation of coating layer) The NaTP obtained in Example 1 or 2 was used and mixed with acetylene black so that the mass ratio of acetylene black to the molar ratio of NaTP was 70:30. Mixing was performed using a planetary ball mill at 400 rpm for 1 hour in an argon atmosphere to form a coating layer made of carbon (carbon layer) on the surface of the NaTP, thereby obtaining NaTP with a carbon layer. (Evaluation of non-aqueous sodium secondary battery characteristics) NaTP with a carbon layer and a conductive binder (product name: TAB-2, manufactured by Hosen Co., Ltd.) were weighed out to a weight ratio of 2:1 and mixed in an agate mortar to prepare a positive electrode mixture. The obtained positive electrode mixture was placed on a SUS mesh (SUS316) with a diameter of 8 mm, and this was subjected to a 1 ton / cm 2 The positive electrode mixture pellets were dried under reduced pressure at 150° C. for 2 hours to obtain a positive electrode.
[0099] Using the obtained positive electrode, a nonaqueous sodium secondary battery having the following configuration was fabricated.
[0100] Test electrode: Positive electrode Counter electrode: Gold (Ag) wire Reference electrode: Silver / silver nitrate (Ag / AgNO3) electrode electrolyte :(Electrolyte)NaPF61mol / dm 3 (Solvent) Ethylene carbonate (EC): Dimethyl carbonate (DMC) =1:1 (volume ratio)
[0101] A constant current charge / discharge test was performed using the nonaqueous sodium secondary battery under the following conditions: Temperature: Room temperature (24.5±2.5℃22~27℃) Electrode potential: -1.63V~1.52V (based on silver / silver nitrate electrode) Current value: 0.4mA / cm 2 Constant current value Number of charge / discharge cycles: 10 The above potential based on the silver / silver nitrate electrode corresponds to 1.50 to 4.65 V based on the sodium electrode.
[0102] As a result of measuring the discharge capacity, the discharge capacity at the first cycle was 147 mAh / g for the nonaqueous sodium secondary battery having NaTP of Example 1 as the positive electrode active material, and 145 mAh / g for the nonaqueous sodium secondary battery having NaTP of Example 2 as the positive electrode active material.
[0103] Measurement example 2 (evaluation of aqueous sodium secondary batteries) (Formation of coating layer) The NaTP obtained in Examples 1 and 2 was used, and a carbon layer (coating layer) was formed on the surface of the NaTP in the same manner as in Measurement Example 1, to obtain NaTP having a carbon layer. (Evaluation of aqueous sodium battery characteristics) NaTP with a carbon layer was used as the positive electrode active material, and this was mixed with AB and PTFE in a weight ratio of 60:30:10 to obtain a pellet-shaped positive electrode mixture with a diameter of 4 mm. An aqueous sodium secondary battery was fabricated with the positive electrode mixture as the working electrode (positive electrode), plate-shaped zinc metal (Zn) as the counter electrode (negative electrode), a silver chloride electrode (Ag / AgCl) as the reference electrode, and an aqueous NaClO4 solution with an electrolyte concentration (NaClO4 concentration) of 15.5 m as the electrolyte. The aqueous sodium secondary battery was charged and discharged under the following conditions, and its discharge capacity was measured.
[0104] Current density: 2mA / cm 2 Voltage: -1.2V~1.3V (vs Ag / AgCl reference electrode) Charge / discharge temperature: room temperature The first cycle discharge capacity was 131 mAh / g for the aqueous sodium secondary battery including NaTP of Example 1, and 128 mAh / g for the aqueous sodium secondary battery including NaTP of Example 2, respectively.
[0105] Measurement example 3 (evaluation of aqueous sodium secondary batteries) The aqueous sodium battery characteristics were evaluated in the same manner as in Measurement Example 2, except that NaTP from Examples 1 and 2 was used, and that a negative electrode using NaTi2(PO4)3 synthesized by the Pechini method as the negative electrode active material was used. The method for producing the negative electrode is shown below. (Preparation of negative electrode) A mixed solution obtained by mixing 40 ml of a solution in which Ti(OCH2CH2CH2CH3)4 was dissolved in a 30% hydrogen peroxide solution, 15 ml of 28% ammonia water, 10 ml of a nitric acid solution of Na2CO3 and citric acid in a molar amount twice that of Ti, 10 ml of an aqueous NH4H2PO4 solution, and ethylene glycol was evaporated to dryness at 80°C for 1 to 2 hours. It was then heated in air at 140°C to obtain a brown gel composition. This was then fired in air at 350°C, and then fired in air at 800°C to obtain NaTi2(PO4)3.
[0106] The obtained NaTi2(PO4)3 and acetylene black (AB) were mixed in a weight ratio of 70:30, and then processed in a planetary ball mill at 400 rpm for 1 hour under Ar atmosphere to carbon-coat the NaTi2(PO4)3 and use it as the negative electrode active material. The obtained negative electrode active material and PTFE were mixed in a weight ratio of 90:10 and molded into pellets with a diameter of 4 mm to use as the negative electrode mixture. (Aqueous sodium secondary battery evaluation) As a result of the evaluation of the aqueous sodium secondary batteries, the discharge capacity at the first cycle was 127 mAh / g for the aqueous sodium secondary battery including NaTP of Example 1, and 127 mAh / g for the aqueous sodium secondary battery including NaTP of Example 2.
[0107] Measurement example 4 (Formation of coating layer) The NaTP obtained in Examples 3 to 6 were used, and a carbon layer (coating layer) was formed on the surface of the NaTP in the same manner as in Measurement Example 1, to obtain NaTP having a carbon layer. (Aqueous sodium secondary battery evaluation) The aqueous sodium battery characteristics were evaluated in the same manner as in Measurement Example 2, except that the obtained NaTP having a carbon layer was used, and that a negative electrode having NaTi2(PO4)3 synthesized by the Pechini method as the negative electrode active material was used.
[0108] As a result of the evaluation of the aqueous sodium secondary batteries, the discharge capacities at the first cycle were 122 mAh / g for the aqueous sodium secondary battery with NaTP of Example 3, 126 mAh / g for the aqueous sodium secondary battery with NaTP of Example 4, 127 mAh / g for the aqueous sodium secondary battery with NaTP of Example 5, and 127 mAh / g for the aqueous sodium secondary battery with NaTP of Example 6.
[0109] Comparative measurement example (non-aqueous sodium ion secondary battery) A sodium-containing transition metal phosphate compound (NaFePO4) having an olivine structure was synthesized according to a method in accordance with Example 1 of JP 2009-206085 A. A pellet-shaped positive electrode mixture was obtained in the same manner as in Measurement Example 2, except that the obtained NaFePO4 was used as the positive electrode active material.
[0110] A nonaqueous sodium secondary battery was produced and subjected to a charge-discharge test in the same manner as in Measurement Example 2, except that the obtained positive electrode mixture was used. As a result, the discharge capacity in the first cycle was 60 mAh / g.
[0111] From these results, it can be confirmed that NaTP of this embodiment shows more than twice the discharge capacity as a positive electrode active material of a nonaqueous sodium secondary battery compared to an olivine-based sodium-containing transition metal phosphate compound. Furthermore, it can be seen from Measurement Examples 1 to 3 that the discharge capacity of the positive electrode active material is lower in an aqueous sodium secondary battery compared to a nonaqueous sodium secondary battery. Nevertheless, it was confirmed that NaTP of this embodiment shows a discharge capacity equal to or greater than that of a nonaqueous sodium secondary battery using a conventional olivine-based sodium-containing transition metal phosphate compound as a positive electrode active material, even when used as a positive electrode active material of an aqueous sodium secondary battery. [Industrial Applicability]
[0112] The sodium transition metal polyanion of the present disclosure can be suitably used as an adsorbent, an ion exchanger, a hydrogen ion conductor, a solid electrolyte, a battery material, in particular, an active material for an electrochemical device, and further, a positive electrode active material for a sodium secondary battery.
Claims
1. General formula Na 3 M 3 (P.O. 4 ) 4 (wherein M is Fe only, or Fe in combination with either Mn or Co), and the crystal structure is monoclinic, and the lattice constants are a is 19.45 Å to 19.75 Å, b is 6.30 Å to 6.45 Å, and c is 10.45 Å to 10.75 Å, β is 90.1° to 93.3°, and a is 19.63 Å or less, b is 6.38 Å or less, or β is 91.5° or less.
2. 2. The sodium transition metal polyanion of claim 1, wherein the monoclinic crystal is a monoclinic crystal belonging to space group C2 / c.
3. The sodium transition metal polyanion has the general formula Na 3 M 3 (P.O. 4 ) 4 3. The sodium transition metal polyanion according to claim 1 or 2, wherein the proportion of powder X-ray diffraction patterns represented by: (wherein M is Fe only, or a combination of Fe with either Mn or Co) is 80% or more.
4. 4. The sodium transition metal polyanion of claim 1, further comprising a coating layer.
5. 5. The method for producing a sodium transition metal polyanion according to claim 1, further comprising a step of subjecting a composition containing a sodium source, a transition metal source, a phosphate source and water and having a pH of 4.0 or more and 11.0 or less to a hydrothermal treatment at 140° C. or more and 250° C. or less.
6. The method according to claim 5 , wherein the pH is 6.0 or more and 9.0 or less.
7. 7. The method according to claim 5 or 6, wherein the transition metal source is at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, phosphates, sulfites, sulfates, nitrates, chlorides, acetates, bromides, and fluorides containing only Fe, or Fe and Mn or Co.
8. A positive electrode active material comprising the sodium transition metal polyanion according to claim 1 .
9. A sodium secondary battery comprising a positive electrode containing the sodium transition metal polyanion according to claim 1 , a negative electrode, and an electrolyte.
10. The negative electrode is at least 2 (P.O. 4 ) 3 The sodium secondary battery according to claim 9 .
11. The electrolyte contains at least NaClO 4 The sodium secondary battery according to claim 9 or 10, comprising:
12. 12. The sodium secondary battery according to claim 9, wherein the electrolytic solution is an aqueous electrolytic solution.
13. The sodium secondary battery according to any one of claims 9 to 11, wherein the electrolytic solution is a non-aqueous electrolytic solution.
Citation Information
Patent Citations
Cathode active material, sodium secondary battery, and manufacturing method of olivine phosphate
JP2009206085A
Aqueous solution secondary battery
JP2011086402A
Secondary battery
JP2014146457A